2021
DOI: 10.1097/phm.0000000000001923
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hand Function and Its Association With Self-Perceived Hand Functional Ability and Quality of Life in Parkinson Disease

Abstract: Objective: Comprehensive hand function in people with Parkinson disease (PD) has been underevaluated. The objectives were to compare self-perceived and objective hand functions of PD and controls, compare outcomes between more and less affected hand subgroups, and evaluate relationship between self-perceived and objective outcomes in subgroups. Design: A total of 165 PD and 82 healthy participants completed the Jebsen-Taylor Hand Function Test, Purdue Pegboard Test, grip strength test, and Manual Ability Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…34 It has also been associated with a decrease in torque production rate. 31 In this study, poor upper extremity performance in the PD group was associated with decreased cervical proprioception. In healthy individuals, the decrease in cervical proprioception was associated with lower upper extremity performance, while the increase in the strength of the deep cervical muscles was associated with higher upper extremity performance.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…34 It has also been associated with a decrease in torque production rate. 31 In this study, poor upper extremity performance in the PD group was associated with decreased cervical proprioception. In healthy individuals, the decrease in cervical proprioception was associated with lower upper extremity performance, while the increase in the strength of the deep cervical muscles was associated with higher upper extremity performance.…”
Section: Discussionmentioning
confidence: 54%
“…Various studies have shown that manual dexterity decreases in individuals with PD compared to healthy individuals. 31,32 Isometric finger torque production and control are affected in PD. 3 In addition, bradykinesia, tremor, rigidity, difficulty in sequential movements, and impaired ability to synchronize and coordinate movements affect manual dexterity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Keramiotou et al ( 22 ) demonstrated a strong association between hand dexterity, performance of daily activities, and quality of life in patients with systemic lupus erythematosus. Similarly, Wong-Yu et al ( 38 ) noted correlations between hand dexterity measures and quality of life in patients with Parkinson’s disease. Both manual dexterity and grip strength were reduced 20%–40% in patients compared to healthy controls, yet only the manual dexterity measures were related to the quality of life measures.…”
Section: Discussionmentioning
confidence: 88%